PENYELESAIAN HUKUM TERHADAP KONSUMEN TOKOPEDIA - Hernando Favian, - (2019)
This thesis discusses Tokopedia's responsibility in carrying out responsibility for consumers, this thesis uses a type of normative legal research, normative law is a method of legal research conducted by examining library material or mere secondary data. And using a normative juridical approach. E-commerce is a modern business model that is non-fice and non-sign. The internet has brought the world economy into a new phase which is more popular with the term digital economy or digital economy. E-commerce has changed the classic business paradigm by growing models of interaction between producers and consumers in the virtual world. The trading system used in e-commerce is designed to sign electronically. This electronic signing was designed from the moment of purchase, inspection and delivery. In the theory of accountability, it is explained that basically everyone will get a reward or reward from the results of their actions or actions and at the same time must be responsible for any consequences arising from their actions or negligence / negligence, in the Indonesian language, the responsibility is to be responsible for everything . Completion of the case was done online through the complaint column found on the Tokopedia website, Tokopedia responded to the problem. Based on recognition from Trendy as a consumer, Elartedelpiano's store finally told Tokopedia to return the money already paid.